Dungeon Code: Educational Game For Algorithm and Data Structure Courses by Applying The Game Development Life Cycle Method - Fakhri Amin; Muhammad Fhadli; Assaf Arief; Yasir Muin (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Algorithm and Data Structure is a basic course in Informatics Study Program, at Khairun University. This subject needs to be mastered because it becomes the foundation that can support the learning process in the future. However, from the results of a survey conducted, as many as 40% of students felt bored with the teaching methods used by Algorithm and Data Structure lecturers in class. In addition, there were also 73.33% of students that even though they paid attention to the material presented in class, they still found it difficult to understand the material. To overcome this problem, new learning media is needed in the classroom, such as games. This study aims to design educational games that teach algorithms and data structures using the Game Development Life Cycle (GDLC) method. The GDLC is a game development method that is widely used to create educational games. The GDLC method has several development stages, namely initiation, pre-production, production, testing, beta, and release. Alpha test results show that all functionality is appropriate. While the results of beta testing show the number 3.43 of the total respondents’ answers to the questionnaire related to game evaluation so they are included in the very good criteria.